Overvoltage risk regulation strategy with distributed energy application in a distribution network based on the Stackelberg game - Qiu, Zekai; Wang, Jianbo; Zhang, Xiaoqing; Lei, Yuhang; Tong, Chenjie; Lu, Yufan; Chang, Xiaoqiang (Frontiers in Energy Research, 2024)
Along with the increasing low-carbon demand of the power system, the access of a high percentage of renewable energy resources to the distribution network has a large impact on the voltage fluctuation of the system and reduces the operational reliability. In this paper, we consider utilizing the reactive capacity of distributed resources to participate in system voltage regulation to reduce nodes loss of load probability (LOLP) caused by node overvoltage fault and propose an overvoltage risk regulation strategy for the interaction between distribution network operators (DSOs) and distributed users in the framework of the Stackelberg game. First, the nodes are clustered and analyzed based on the twodimensional indexes of node voltage regulation ability, and different voltage regulation compensation tariffs are assigned. Secondly, the cost and benefit model of voltage regulation for leader and follower sides, and the node LOLP model are constructed to measure the reliability of the system. The Stackelberg game is used to achieve the co-optimization of the two parties' compensation tariffs and voltage regulation strategies, the optimal solution of voltage regulation under the equilibrium of game is obtained by solving using the PSO algorithm. Based on the IEEE-33 node system, a case study is carried out to verify that the proposed overvoltage risk regulation strategy can maximize the benefits of the regulator participants while enhancing the operational reliability of the system.